2004
DOI: 10.1080/13561820410001686918
|View full text |Cite
|
Sign up to set email alerts
|

Towards interprofessional family-oriented teamwork in primary services: the evaluation of an education programme

Abstract: A 2-year interprofessional family-oriented training programme for professionals working in the field of primary services (e.g. health care, social welfare, schools, day care) started in Oulu Province, Finland, in 2000. It aimed to provide the trainees with skills to work with families in interprofessional teams, to support them to cope better and to encourage them to develop new models for helping clients. Seventy-six trainees from 13 professions participated. This paper describes the structure, methods and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…The findings of this systematic review and meta‐analysis have reported significant improvements in pre‐ and post‐status scores after embedding IPE module in various medical fields as determined by enhanced acquisition of knowledge, skills, and attitudes of learners. This effectiveness of IPE pre‐post design has been proposed to carry multi‐dimensional gains; IPE has been shown to increase job satisfaction among emergency department nurses and physicians [32], has helped the primary health care practitioners in their approach to resolve complex issues with clients and their ability to utilize other resources [33], and has been instrumental in dispelling stereotypes [34]. Turner has argued that medical and allied health students may pass their courses and programs and may enter their practical careers with certain perceptions or understandings of other professions that may or may not be accurate [35].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this systematic review and meta‐analysis have reported significant improvements in pre‐ and post‐status scores after embedding IPE module in various medical fields as determined by enhanced acquisition of knowledge, skills, and attitudes of learners. This effectiveness of IPE pre‐post design has been proposed to carry multi‐dimensional gains; IPE has been shown to increase job satisfaction among emergency department nurses and physicians [32], has helped the primary health care practitioners in their approach to resolve complex issues with clients and their ability to utilize other resources [33], and has been instrumental in dispelling stereotypes [34]. Turner has argued that medical and allied health students may pass their courses and programs and may enter their practical careers with certain perceptions or understandings of other professions that may or may not be accurate [35].…”
Section: Discussionmentioning
confidence: 99%
“…The effects on the IPCP were little studied (Cooper et al . , Larivaara & Taanila ). Only few studies related to the effects of IPE and IPCP in hospital or community setting, but not in school setting, were searched (Reeves & Freeth , Reeves et al .…”
Section: Discussionmentioning
confidence: 94%
“…However, their research canons mainly focused on participants' gained knowledge, changed attitudes and beliefs through IPE and IPCP. The effects on the IPCP were little studied (Cooper et al 2001, Larivaara & Taanila 2004. Only few studies related to the effects of IPE and IPCP in hospital or community setting, but not in school setting, were searched .…”
Section: Discussionmentioning
confidence: 99%
“…Management of such issues requires development of new interviewing strategies and different ways to use the visit time more effectively [24]. Finnish experience shows that after completing an education programme, the family doctors' became more family-oriented and family doctors satisfaction with their work was also increased [25]. …”
Section: Discussionmentioning
confidence: 99%